Inventory of John Blower's Papers. Ethiopian Wildlife Conservation Authority (EWCA) Library, Addis Ababa (Ethiopa) - Rigaldès, Pia; Blanc, Guillaume (My University, 2022)
John Blower was the first advisor of the Ethiopian Wildlife Organisation between 1965 and 1970. This new Ethiopian administration has been established after the Emperor Hailé Selassié requested assistance from UNESCO about wildlife issues. Graduated at the Edinburgh University, John Blower had several African wildlife experiences before joining Ethiopia in 1965: he has been game ranger in Tanganyiaga, in Kenya and chief game warden in Uganda. As advisor of the wildlife organisation in Ethiopia, he took part during five years in the creation of the first national parks in Ehiopia in 1969: the Awash, Semien and Omo parks. All the documents which are present in this collection are directly or indirectly the result of John Blower’s activities in this administration.
Keywords: Ethiopia; Wildlife; National Parks Management